Prospective comparison of laparoscopic and traditional colposuspensions in the treatment of genuine stress incontinence - Tsung‐Hsien Su; Kuo‐Gon Wang; Chin‐Yuan Hsu; Hsiao‐Jui Wei; Bin‐Kuan Hong (Acta Obstetricia et Gynecologica Scandinavica)
Objective. To compare prospectively the results of laparoscopic and traditional colposuspensions in the treatment of genuine stress incontinence and to evaluate the efficacy, technique, and functional and anatomical changes after these two procedures. Materials and methods. Ninety‐two patients with urodynamically proven genuine stress incontinence participated in this study, with 46 patients randomly allocated to laparoscopic colposuspension, and the other 46 patients to the traditional procedures. All patients had repeat studies at least 3 months after operation. Results. The bladder neck position was significantly elevated after operation either at rest or during straining in both groups (all p<0.001), but it was higher in the traditional group than the laparoscopy group during straining (p<0.05). Comparison of urodynamics before and after operation in both groups showed significantly increased minimal urethral resistance and improved pressure transmission ratios at the proximal urethra (Q2). The blood loss was less in the laparoscopy group. The duration of bladder drainage after laparoscopic colposuspension was shorter, and was not affected by subsequent laparotomy. The operative time was almost the same. The success rate of the laparoscopy group was lower than that of the traditional group (80.4% vs. 95.6%, p=0.044). The complication rates were 10.8% and 17.4% respectively. Conclusion. Laparoscopic colposuspension is an effective method for the treatment of GSI, as documented by anatomical and functional assessments. However, the success rate is still lower than for the traditional procedure.